B. subtilis CNBG‐PGPR‐1 induces methionine to regulate ethylene pathway and ROS scavenging for improving salt tolerance of tomato - Feng, Liuchun; Li, Qi; Zhou, Dongqin; Jia, Mingyun; Liu, Zhuangzhuang; Hou, Zhaoqi; Ren, Quanjin; Ji, Shengdong; Sang, Shifei; Lu, Shipeng; Yu, Jinping (The Plant journal : for cell and molecular biology, 2024)
SUMMARY Soil salinity severely threatens plant growth and crop yields. The utilization of PGPR is an effective strategy for enhancing plant salt tolerance, but the mechanisms involved in this process have rarely been reported. In this study, we investigated the effects of Bacillus subtilis CNBG‐PGPR‐1 on improving plant salt tolerance and elucidated the molecular pathways involved. The results showed that CNBG‐PGPR‐1 significantly improved the cellular homeostasis and photosynthetic efficiency of leaves and reduced ion toxicity and osmotic stress caused by salt in tomato. Transcriptome analysis uncovered that CNBG‐PGPR‐1 enhanced plant salt tolerance through the activation of complex molecular pathways, with plant hormone signal transduction playing an important role. Comparative analysis and pharmacological experiments confirmed that the ethylene pathway was closely related to the beneficial effect of CNBG‐PGPR‐1 on improving plant salt tolerance. Furthermore, we found that methionine, a precursor of ethylene synthesis, significantly accumulated in response to CNBG‐PGPR‐1 in tomato. Exogenous L‐methionine largely mimicked the beneficial effects of CNBG‐PGPR‐1 and activated the expression of ethylene pathway‐related genes, indicating CNBG‐PGPR‐1 induces methionine accumulation to regulate the ethylene pathway in tomato. Finally, CNBG‐PGPR‐1 reduced salt‐induced ROS by activating ROS scavenger‐encoding genes, mainly involved in GSH metabolism and POD‐related genes, which were also closely linked to methionine metabolism. Overall, our studies demonstrate that CNBG‐PGPR‐1‐induced methionine is a key regulator in enhancing plant salt tolerance through the ethylene pathway and ROS scavenging, providing a novel understanding of the mechanism by which beneficial microbes improve plant salt tolerance. Significance Statement The utilization of plant growth‐promoting rhizobacteria (PGPR) is an effective strategy for enhancing plant salt tolerance, but only a few mechanisms involved in this process have been identified so far. The present study showed methionine induced by Bacillus subtilis CNBG‐PGPR‐1 is a key regulator to enhance plant salt tolerance through the ethylene pathway and ROS scavenging, providing a novel understanding of the mechanism by which beneficial microbes improve plant salt tolerance.